Influence of nano additives on performance, combustion, and emission characteristics of diesel engine using tamarind oil methyl ester-diesel fuel blends / Bikkavolu Joga Rao ... [et al.] - Bikkavolu, Joga Rao; Pullagura, Gandhi; Vadapalli, Srinivas; Chebattina, Kodanda Ramarao; Pathem, Uma Chaithanya (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Hazardous emissions majorly NOx and the poor performance of alternative fuels (biodiesel/its blends) are global concerns, as fossil fuel depletion and rising energy prices encourage researchers to rely on alternative energy sources with the addition of nano additives in the recent decade. The current experimental study investigates the performance, combustion, and emission characteristics of biodiesel-diesel mixtures dispersed with titanium dioxide (TiO2) as a fuel additive on a 1-cylinder diesel engine. TiO2 was dispersed in a Tamarind Oil Methyl Ester (TOME)-diesel blend (B20) in three concentrations of 40, 80, and 120 ppm via ultrasonication in the presence of QPAN80 surfactant to enhance the stability of the prepared fuel sample. A ratio of 1:4 TiO2:QPAN80 was found to produce the highest stability and homogeneity which is evidenced by the characterization of TiO2. The engine tests revealed that the greatest decrement in BSFC, CO, HC, and NOx was observed as 15.2%, 15.2%, 11.10%, and 9.06%, and the maximum BTE, HRR,